Duplex-Doppler ultrasound evaluation of intrapancreatic blood flow in patientswith insulin-dependent diabetes mellitus - Drinković, Ivan (Radiology and oncology (Ljubljana), 2000)
Background. The purpose of the study was to assess the value of pulse-wave andcolor-Doppler ultrasound (CDUS) in estimation of the pancreatic blood flow,and to test the hypothesis that accelerated atherosclerosis in insulin-dependent diabetes mellitus (IDDM) causes an increased vascular resistance. Patients and methods. Gastroduodenal arteries in 40 patients with IDDM and 30 healthy volunteers were insolated, and resistance index (RI) and pulsatility index (PI) were assessed. The statistical significance of the difference between Doppler indices among examined groups, as well as the correlation with the age, sex and duration of the disease were tested. Results. In the group, median RI was 0.71 and median PI was 1.46. In IDDM patients group median RI was 0.74 and median PI was 1.54. The differences between these Doppler indices were not significant, with a p=0.82 for RI, and p=0.74 for PI. Also, no significant correlation was observed RI and PI and theduration of the disease. Conclusions. CDUS is simple noninvasive imaging modality for the estimation of blood flow in the gastroduodenal artery, which,in our work, did not prove to be of particular value in the assessment of pancreatic flow in IDDM patients.
Keywords: arterije; Atherosclerosis; Blood supply; Diabetes mellitus, insulin-dependent; diagnostika; krvni obtok; Mesenteric artery, superior; Pancreas; sladkorna bolezen; trebušna slinavka; Ultrasonography; Ultrasonography, doppler, duplex; Ultrasonography, doppler, pulsed; ultrazvočna diagnostika